Management in the digital era : different perspectives - Erten, Serafettin; Çögenli, Mehmed Zahid (Management science--theory and applications series., 2023)
"This book reveals the impact of the digital transformation on management, which has accelerated with the new digital age. The digitalization process, which is advancing rapidly in the world, creates a lasting impression and sea of changes in management activities. The studies done include research that evaluates many aspects of digital transformation in the management activities of organizations. The book consists of 17 chapters, with the contribution of 21 scholars, discussing various management activities and strategies in terms of digital transformation in many disciplines from the point of content and extent"--